2016
DOI: 10.1007/s10654-016-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal exposure to cadmium on cognitive development at preschool age and the importance of selenium and iodine

Abstract: The evidence regarding a potential link of low-to-moderate iodine deficiency, selenium status, and cadmium exposure during pregnancy with neurodevelopment is either contradicting or limited. We aimed to assess the prenatal impact of cadmium, selenium, and iodine on children’s neurodevelopment at 4 years of age. The study included 575 mother–child pairs from the prospective “Rhea” cohort on Crete, Greece. Exposure to cadmium, selenium and iodine was assessed by concentrations in the mother’s urine during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…However, other studies failed to find any significant association with these and other assessed aspects of neuropsychological development in children from Greece (Kippler et al, 2016), USA (Oken et al, 2016), Poland (Polanska et al, 2016) and Japan (Tatsuta et al, 2017). Se levels (mean ± standard deviation) observed in these studies were 23 ± 8.6 µg/L in maternal urine at the first trimester of pregnancy in Greece (Kippler et al, 2016), 205.6 ± 34.6 ng/mL in erythrocytes at mid-pregnancy in USA (Oken et al, 2016), and 66.3 ± 10.2 and 67.0 ± 9.6 ng/g (for boys and girls, respectively) in cord plasma in Japan (Tatsuta et al, 2017). Conversely, Saint-Amour et al (2006) observed that prenatal Se levels were associated with alterations in the visual evoked potentials of Inuit children (cord blood Se was 4.44 ± 2.08 µmol/L) (Saint-Amour et al, 2006).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, other studies failed to find any significant association with these and other assessed aspects of neuropsychological development in children from Greece (Kippler et al, 2016), USA (Oken et al, 2016), Poland (Polanska et al, 2016) and Japan (Tatsuta et al, 2017). Se levels (mean ± standard deviation) observed in these studies were 23 ± 8.6 µg/L in maternal urine at the first trimester of pregnancy in Greece (Kippler et al, 2016), 205.6 ± 34.6 ng/mL in erythrocytes at mid-pregnancy in USA (Oken et al, 2016), and 66.3 ± 10.2 and 67.0 ± 9.6 ng/g (for boys and girls, respectively) in cord plasma in Japan (Tatsuta et al, 2017). Conversely, Saint-Amour et al (2006) observed that prenatal Se levels were associated with alterations in the visual evoked potentials of Inuit children (cord blood Se was 4.44 ± 2.08 µmol/L) (Saint-Amour et al, 2006).…”
Section: Discussionmentioning
confidence: 86%
“…Very few prospective studies have evaluated the relationship between Se status during pregnancy and child neuropsychological development among populations with intermediate Se levels and the results obtained have been heterogeneous. Thus, positive, negative and null effects on child neuropsychological development have been observed in relationship to prenatal Se levels (Amorós et al, 2018;Kippler et al, 2016;Oken et al, 2016;Polanska et al, 2016;Skröder et al, 2015;Yang et al, 2013) and, in addition, the shape of this association has scarcely been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Quality control was performed by including commercial reference materials for urine [Seronorm™ Trace Elements Urine Blank OK4636, Seronorm™ Trace Elements Urine NO2525, Seronorm™ Trace Elements Urine 1011644, Seronorm™ Trace Elements Urine 1011645 and National Institute of Standards and Technology (NIST) Standard Reference Material® 2670a], and the results for these samples were in line with recommended values (see Table S1). We also measured concentrations of arsenic, cadmium, and lead in urine at both 5 and 10 y, and we measured concentrations of manganese in drinking water collected at the 10-y follow-up ( Kippler et al 2012 , 2016 ). All concentrations in urine were adjusted to the average specific gravity (1.012) to compensate for variations in dilution ( Nermell et al 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, Cd levels in cord blood are typically lower than maternal Cd levels [40]. Nevertheless, in utero Cd exposure has been linked to a range of adverse health effects, including impaired growth and neurodevelopment [41][42][43]. To date, one study has examined the relationship between global DNA methylation and prenatal Cd exposure.…”
Section: Cadmiummentioning
confidence: 99%